Brain amyloid β protein and memory disruption in Alzheimer’s disease - Weiming Xia (Dove Medical Press, 2010)
Weiming XiaCenter for Neurologic Diseases, Department of Neurology, Brigham and Women’s Hospital and Harvard Medical School, Boston, MA, USAAbstract: The development of amyloid-containing neuritic plaques is an invariable characteristic of Alzheimer’s diseases (AD). The conversion from monomeric amyloid β protein (Aβ) to oligomeric Aβ and finally neuritic plaques is highly dynamic. The specific Aß species that is correlated with disease severity remains to be discovered. Oligomeric Aβ has been detected in cultured cells, rodent and human brains, as well as human cerebrospinal fluid. Synthetic, cell, and brain derived Aβ oligomers have been found to inhibit hippocampal long-term potentiation (LTP) and this effect can be suppressed by the blockage of Aβ oligomer formation. A large body of evidence suggests that Aβ oligomers inhibit N-methyl-D-aspartate receptor dependent LTP; additional receptors have also been found to elicit downstream pathways upon binding to Aβ oligomers. Amyloid antibodies and small molecular compounds that reduce brain Aβ levels and block Aβ oligomer formation are capable of reversing synaptic dysfunction and these approaches hold a promising therapeutic potential to rescue memory disruption.Keywords: Alzheimer, amyloid, oligomer, long-term potentiation, NMDA